Pengaruh Tax Avoidance dan Intensitas Modal Terhadap Pajak Penghasilan Badan Terutang Dimoderasi Kepemilikan Manajerial - Rahmad Tuahji; Iman Indrafana Kusumo Hasbulla (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2025)
This research aims to determine tax avoidance and capitalintensity on corporate income tax payable with managerialownership as a moderating variable in manufacturingcompanies in the goods and consumption industry sector listedon the Indonesia Stock Exchange in 2020 - 2024. The sampleselection method used is purposive sampling. The total observations in this research were 120 samples with 5 years ofobservation consisting of 24 companies. The data analysistechnique used in this research is multiple linear regressionanalysis and moderation analysis using the ModeratedRegression Analysis approach. The results showed that taxavoidance affects corporate income tax payable, while capitalintensity cannot affect. Managerial ownership is able tomoderate the effect of tax avoidance on corporate income taxpayable, while managerial ownership is not able to moderatecapital intensity.